Dampak Teknologi Komunikasi Terhadap Pernikahan Dini Di Kecamatan Blangkejeren-Gayo Lues - Taufik; Shania Naurita; Jasafat (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Many teenagers access pornography without any education about sexual behavior. Minimal understanding of sex and easy access to pornography encourage teenagers to try new experiences. The case of early marriage in Blangkejeren District, Gayo Luwees Regency is very worrying. The purpose of this research was to find out what aspects of communication technology can influence the occurrence of early marriage and the impact of communication technology on early marriage. The method used in this research is qualitative. This research uses a phenomenological approach, namely seeing and hearing phenomena that occur naturally more closely and in detail. Data was obtained by observation, interviews and documentation. The results of this research show that social media with pornographic content is an aspect of communication technology that can have a negative impact, influencing teenagers' thought patterns and behavior which can lead to early marriage.